Data mining : practical machine learning tools and techniques - Witten, Ian H.; Frank, Eibe; Hall, Mark A. (Amsterdam : Elsevier, 2011)
Data Mining: Practical Machine Learning Tools and Techniques, Third Edition , offers a thorough grounding in machine learning concepts as well as practical advice on applying machine learning tools and techniques in real-world data mining situations.
Part I. Introduction -- Part II. Advanced data mining -- Part III. The Weka data mining workbench.
Includes bibliographical references and index.
Keywords: DATA MINING